Differences level of injury severity for male and female drivers in traffic crashes in Sabah - Rusli, Rusdi; Mohd Masirin, Mohd Idrus; Abdul Hamid, Norashikin (Research Gate, 2020)
Road traffic crash has become a big issue around the world because it has recorded a higher number of fatalities each year. Previous research has found many factors influencing injury severity between male and female drivers. However, these factors might be different in complex driving condition like mountainous areas and different vehicle composition. The main objective of this study is to examine the differences between male and female driver’s injury severity in a passenger car, four-wheel drive vehicle and van. In order to investigate the effect of topography and vehicle composition, Sabah has been selected as the study area. Separate logistics regression model for injury severity of male and female drivers were examined using traffic crash data from 2008 to 2012. The results showed that the crashes at night times and wet season were more severe than crashes on day time and dry season for male drivers only. Crashes on cross junction were more severe for female drivers. Dangerous turning behaviours that cause the crashes also contributed to the increasing severity level of female drivers. Factors which have the same effect on male and female drivers were collision type, road type, road geometry, driver age, driver errors and type of vehicle. This study gives an insightful understanding about the different factors influencing injury severity level, which involved male and female drivers in crashes in areas that are mountainous and the effect of different vehicle composition on the road.